Research on "Recruitment, Education and Retention" All-chain Cultivation Path of Wenzhou’s Local Skilled Talents with School-Industry Collaboration - Zheng, Xiaodan (International Journal of Social Sciences and Public Administration, 2024)
Talent is the key element to promote the regional economic development and realize the enhancement of regional capacity. At present, Wenzhou City is promoting the construction of "Double Ten Thousand" city, how to nurture local talents and attract external talents is the most urgent task. By exploring the implementation of school-industry cooperation in Wenzhou, this study constructs a complete set of local talent attraction, cultivation and retention through the in-depth analysis of the three modules of "enrollment", "cultivation" and "retention". Through in-depth analysis and discussion of the three modules of "enrollment", "cultivation" and "retention", we have constructed a complete set of local skilled personnel attraction, cultivation and retention of the whole chain of cultivation paths, and given the policy suggestions that can be popularized and replicated, to further promote the realization of the goal of "enrollment of local", "cultivation of local", "retention of local It further promotes the realization of the goal of "recruiting local students", "cultivating local talents" and "retaining local talents", and provides strong intellectual support for the economic and social development of Wenzhou.